How to market a regional airport? - Watkins, Marc (Henry Stewart Talks, 2009)
Market position, Passenger traffic, Top ten routes, Competitive catchment, Customer marketing, Key attractions and key factors for airlines, Market potential data, Key factors for passengers, Customer marketing for passengers and travel agents